Undiagnosed hypertension and associated factors among older adults in Gedeo zone, southern Ethiopia: A mixed methods approach - Tsion Mulat Tebeje; Mihret Fikreyesus; Temesgen Leka Lerango; Daniel Sisay (PLoS ONE, 2025)
Background Hypertension often goes undetected for years because its initial symptoms are usually subtle and easily overlooked. Undiagnosed hypertension is a significant contributor to the onset of cardiovascular disease, renal disease, and overall mortality. Although its prevalence increases with age, few studies have investigated the factors associated with undiagnosed hypertension in older adults. Therefore, this study aimed to identify factors influencing undiagnosed hypertension among older adults in the Gedeo zone, Southern Ethiopia. Methods A study design incorporating a community-based cross-sectional study and qualitative inquiry as a complementary approach was carried out among 609 randomly selected older adults in the Gedeo zone from March 19 to May 20, 2023. A binary logistic regression model assessed the relationships between the outcome and explanatory variables, with statistical significance set at a p-value of < 0.05. The qualitative data were transcribed, translated into English, and analyzed using Open Code version 4.03. Results The prevalence of undiagnosed hypertension among older adults was 39.24% (95% CI: 35.43%, 43.19%). The determinants that were found to have a significant relationship with undiagnosed hypertension were living in urban areas (AOR = 0.54, 95% CI: 0.34, 0.83), being able to read and write (AOR = 0.21, 95% CI: 0.11, 0.38), attending primary education and above (AOR = 0.53, 95% CI: 0.32, 0.87), not having a health seeking behavior (AOR = 2.26, 95% CI: 1.48, 3.43), being overweight or obese (AOR = 4.50, 95% CI: 2.74, 7.39), having chronic diseases (AOR = 1.72, 95% CI: 1.11, 2.66), and having a family history of hypertension (AOR = 1.90, 95% CI: 1.13, 3.21). Conclusion Our findings showed that about four out of 10 older adults in the Gedeo zone have had undiagnosed hypertension. This highlights the need for a comprehensive and precise screening program for these vulnerable population. In-depth interviews revealed that television programs and healthcare providers were major sources of information regarding hypertension and its prevention methods. Therefore, it is crucial to prioritize preventive interventions and develop appropriate programs focused on older adults. In particular, people with chronic diseases and a family history of hypertension should be taught and encouraged to undergo timely checkups.